Real Time Sticky Bomb Detection System Based on Compass Device and Arduino Board - Majeed, Sameer Hameed; Jumaa, Noor Kareem; Mohamad, Auday A.H. (Iraqi Journal for Electrical and Electronic Engineering, 2017)
This paper presents a new strategy of sticky bomb detection. The detection strategy is based on measuring the magnetic field around the targeted car using compass device. A compass measure the earth gravitation of the car as (x,y,z) coordination , a threshold value of magnetic fields around the targeted car are recorded. If a difference is detected with any (x,y,z) coordination, an alert SMS message is sent to the car's owner. The detection system presented in this paper has been implemented based on Arduino board. The alarm signal is a Short Message Service (SMS) through Global System for Mobile Communication (GSM) module. The proposed method can gives the people of unstable countries a chance to discover whether their cars have been trapped with an IED bomb or their car still safe.